If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(4n + 4) = -6 Reorder the terms: 5(4 + 4n) = -6 (4 * 5 + 4n * 5) = -6 (20 + 20n) = -6 Solving 20 + 20n = -6 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 20n = -6 + -20 Combine like terms: 20 + -20 = 0 0 + 20n = -6 + -20 20n = -6 + -20 Combine like terms: -6 + -20 = -26 20n = -26 Divide each side by '20'. n = -1.3 Simplifying n = -1.3
| 5x-32+89=180 | | 7x+22= | | c=2x | | 4x+8x+16x+6x-x=11 | | X+17=56 | | 2a+s=294 | | 100-7r= | | -5x+2(x-3)=-2(x-3) | | 0.2x+10-6=1.2x+8 | | 7v-2v-v-3v=14 | | b+2+6=7 | | (-1)x(-3)= | | 4a+2s=588 | | -6-5x=-26 | | 15z-12z-2z=15 | | 3(6e-4)=e+4 | | 7(x+2)-5=7x+9 | | 4(10x-8)=x+9 | | 18y+y-14y-2y+2y=15 | | 5x+7x+14=31 | | X+9=-x+11 | | x=4y+10 | | 0+0.99X=10+0.89X | | (x-6)(x+11)=0 | | 460+x=x | | 10(9k-1)=k+9 | | -8j+4j=12 | | (x+5)(x+5)(3x-5)=0 | | 4x^2-32x-8=0 | | 4x-15+15x+5=180 | | 2y+8=22y | | 14n-2n+n-12n=11 |